Black Unsettlement. Embodied Blackness and Black Studies in the Irish Context - Mullen, Mary (My University, 2024)
Reflecting the call for diverse opinions in knowledge production, this article is a personal perspective on the positioning of Black Studies in Ireland. Black Studies as praxi-theory foregrounds the inseparability of embodied experiences from epistemic subject, since the knowledge production process is inherently subjective. Within the Irish racial ecology, the specificities of being Black suggest using the term anti-blackness rather than racism to address systemic racial violence against the Black body. While the presence of blackness in Ireland challenges imagined narratives of racial homogeneity, anti-blackness is deeply entrenched within academic texts, materials and ideas, shaping knowledge production cultures and systems. To understand the nature of anti-blackness in Ireland, a number of concepts which inform the author's work will be introduced. Xeno/miso-phenotypic prejudice encompasses both bias and aversion in relation to the Black body. Unexpected Irishness reflects the dissonance in some imagined white spaces, discourses and epistemes when confronted by the onto-epistemological totality of blackness. The author, positioned as a Black academic teaching Black Studies, underscores the potential tokenisation of Black scholarship within Higher Education Institutions and the toll on Black academics’ well-being. The text calls for a genuine elevation of Black Studies, acknowledging its power to unsettle academic complacency.
PUBLISHED
Invited contribution on critical race/Black Studies
Keywords: Research Subject Categories::SOCIAL SCIENCES; Black studies, epistemic erasure, anti-blackness, embodied blackness, extraversion; Identities in Transformation; Inclusive Society; Identity politics and social change; Race and ethnic studies; Sociological Theory